Peer enterprises: design and implementation of a cross-organisational peer-to-peer framework. (1st January 2013) - Gupta, Ankur; Awasthi, Lalit K.
P2P networks are considered too transient in nature and vulnerable to security attacks to be deployed in catering to many organisational requirements including cross-organisational collaborations. Hence, we find very few real-world applications of P2P networks beyond content sharing and communication, although the research community is actively engaged in applying the P2P concept to build some novel applications. This research paper presents the design, implementation and some early results for the 'peer enterprises' framework, a novel cross-organisational P2P application facilitating resource/services exchange across organisations in a secure and transparent manner. From the results, we conclude that such a framework is entirely viable and feasible for deployment in an enterprise environment and can help solve a real-world need without requiring extensive investment in additional computing infrastructure.